The Effect of Job Training and Attendance on Employee Performance at Pt Bank Central Asia Regional Office IV Denpasar Area Service Center - Meganein, Dewa Ayu Komang Sonia; Yudistira, Cokorda Gede Puta; Sarjana, I Made; Kasiani, Kasiani; Marheni, Lili (Business Management, 2024)
Abstract: The problem of cultivating Skills and absenteeism is important to study, because these two things are the fundamental factors that affect employee performance. Job training and attendance are the initial basis for an employee to become skilled in their field and achieve increased performance. So, in this study the authors formulate the main problem, how much job training affects the performance of BCA Regional Office IV Denpasar Service Centre employees, how much Absenteeism affects the performance of BCA Regional Office IV Denpasar Service Centre employees, and how much Job Training and Absentee-ism affect BCA employee performance Kanwil IV Denpasar Service Centre. Data collection methods used are observation, questionnaires and literature study. The samples in this study were 66 employees. The analysis technique used is multiple linear regression analysis. The results of the study show that job training and work absences have a simultaneous effect on performance by 65.5%. The correlation coefficient between job training and absenteeism on performance is a very strong relationship of 0.809. The output of this study is in the form of posters that motivate employees to continue to improve their abilities through job training and maintain discipline through work attendance